Papier im mittelalterlichen Europa: Herstellung und Gebrauch - Meyer-Schlenkrich, Carla; Schultz, Sandra; Schneidmüller, Bernd (Materiale Textkulturen, 2015)
Researchers view the switch from parchment to paper as an essential condition for the rapid rise in literacy in Europe during the Late Middle Ages. The first part of this volume focuses on medieval paper production in the mill districts in Northern Italy, Southwestern Germany, and Belgium. The second part examines the displacement of parchment by paper in administration and in book culture.
Beitr. teilw. dt., teilw. engl. - Mit engl. Zsfssgn der Beitr
Keywords: Geschichte 1100-1500; Aufsatzsammlung; Konferenzschrift -- 2013 -- Heidelberg; Papiermühle; Papierherstellung; Europa